Generasi Remaja Bebas Diabetes melalui Edukasi Pola Hidup Sehat di Sekolah - Zulkifli Walangadi; Jasmin Ambas; Nurul Anisa; Samsiana; Irwandi Rachman (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
Diabetes mellitus is a non-communicable disease with a continuously increasing prevalence and poses a significant public health challenge. Early prevention efforts, particularly among junior high school adolescents, are essential to reduce the risk of developing diabetes in adulthood. This community service activity aimed to improve students’ knowledge of diabetes prevention through the adoption of a healthy lifestyle. The activity was conducted among 23 ninth-grade students at SMP Negeri 3 Bontonompo Selatan Satap Salajo. A pre-experimental design using a one group pretest–posttest approach was applied. The intervention consisted of contextual and interactive health education delivered through lectures, discussions, and question-and-answer sessions. Students’ knowledge levels were assessed using a 10-item questionnaire administered before and after the educational intervention. The results demonstrated an improvement in students’ knowledge, indicated by an increased proportion of students categorized as having good knowledge and a rise in the mean knowledge score from 59.13 in the pretest to 70 in the posttest. These findings indicate that school-based health education is an effective promotive and preventive strategy for early diabetes mellitus prevention.